2019
DOI: 10.1016/j.ygeno.2018.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial genome characteristics of Somena scintillans (Lepidoptera: Erebidae) and comparation with other Noctuoidea insects

Abstract: In this study, mitogenome of Somena scintillans (Lepidoptera: Erebidae) were sequenced and compared with other Noctuoidea species. The mitogenome is 15,410 base pairs in length. All 13 protein-coding genes (PCGs) are initiated by ATN codons except cox1 with CGA and all of PCGs terminate with TAA except nad4 with TAG. The codons ACG and CGC are absent. All the tRNA genes could be folded into the typical cloverleaf secondary structure except the trnS1 which not only loses dihydrouridine (DHU) arm but also mutate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 36 publications
2
4
0
Order By: Relevance
“…were terminated by TAA. Our findings are consistent with those of Liu et al [55], Dai et al [22], Dai et al [56], Li et al [57] Chen et al [58] and Riyaz et al [48] who also reported the presence of single "T" as a termination codon for the cox1 and cox2 genes in the majority of Lepidopteran species. This incomplete termination codon "T" in lepidopteran mt genes might get polyadenylated to TAA codon during translation [46,47,59].…”
Section: Plos Onesupporting
confidence: 93%
“…were terminated by TAA. Our findings are consistent with those of Liu et al [55], Dai et al [22], Dai et al [56], Li et al [57] Chen et al [58] and Riyaz et al [48] who also reported the presence of single "T" as a termination codon for the cox1 and cox2 genes in the majority of Lepidopteran species. This incomplete termination codon "T" in lepidopteran mt genes might get polyadenylated to TAA codon during translation [46,47,59].…”
Section: Plos Onesupporting
confidence: 93%
“…For trnS1 (AGN), the TCT is used instead of routinely used codon GCT. This phenomenon has been recognized in previous reports such as two species of Hepialoidea and three species of Noctuoidea (Li et al 2018). In trnK , the mostly used anticodon CTT was changed to TTT (Wu et al 2012), which is, to our knowledge, extremely rare in Lepidoptera and insects in general.…”
Section: Resultssupporting
confidence: 74%
“…This lack of GC-rich codons is common to many other Lepidopterans including H. cunea (GCG and GTG), P. atrilineata (CGG), and C. pomonella (GCG). Utilized codons showed a bias towards A + T content, contributing to the overall mitogenomic AT-bias that was observed both in S. retorta and across other insect mitogenomes 19,22 .…”
Section: Resultsmentioning
confidence: 96%
“…The TAA stop codon was the most common among these PCGs (nad2, cox1, atp8, atp6, cox3, nad3, nad5, nad4L, nad6, cytb), while nad1 utilized a TAG stop codon, and nad4 and cox2 harbored incomplete stop codons (T) (Table 1). This is a common conserved mitogenomic feature among invertebrates [17][18][19] , and this single T residue can be still be recognized by endonucleases during polycistronic pre-mRNA transcription, with polyadenylation from contiguous PCGs ultimately yielding a functional stop codon 5,20,21 . Next, we assessed codon usage among a range of Lepidopteran species, including three Noctuoidae members as well as Bombycoidea, Tortricoidea, and Geometroidea members (Fig.…”
Section: Resultsmentioning
confidence: 99%